Anything Goes Ala Paul Feyerabend, Pendidikan Finlandia Sampai Ke Nadiem Makarim - Dani Firmanto Simanjuntak (Marturia, 2023)
Abstract I, as a [college] student of Indonesian standard education products, have experienced a barren of knowledge because of the ‘doctrine’ system in accordance with the prevailing interests in the Indonesian education system. Learning from the principle of anything goes, Feyerabend disassembles all projections of the unity of science and theory in the division of reality into an open space for other studies or theories. Freedom is the right word to express and actualize human beings themselves with others. The education system, which consists of scientific content, is an effort to liberate humans but is trapped in a system that enslaves them. Students no longer learn ‘for’, but learn ‘from’ which restrains them as humans playing (homo ludens) and learning. I compare Finnish education with Indonesian education, as an effort called Nadiem Makarim, simultaneous and moving changes. Abstrak Saya sebagai [maha] siswa produk pendidikan baku Indonesia selama ini mengalami kemandulan ilmu pengetahuan karena sistem ‘doktrin’ sesuai dengan kepentingan yang berlaku di dalam sistem pendidikan Indonesia. Belajar dari prinsip anything goes, Feyerabend membongkar semua proyeksi kesatuan ilmu dan teori di dalam kepelbagian realitas menjadi ruang terbuka untuk kajian-kajian atau teori yang lainnya. Kebebasan adalah kata yang tepat untuk mengekspresikan dan mengaktualisasikan diri manusia itu sendiri dengan yang lain. Sistem Pendidikan yang di dalamnya terdiri muatan ilmu pengetahuan adalah upaya membebaskan manusia, tetapi terjebak dalam sistem yang memperbudak. Siswa tidak lagi belajar ‘untuk’, tetapi belajar ‘dari’ yang mengekang dirinya sebagai manusia bermain (homo ludens) dan belajar. Saya membandingkan pendidikan Finlandia dengan Pendidikan Indonesia, sebagai upaya yang disebut Nadiem Makarim, perubahan yang serentak dan bergerak.